Familial Congenital Hyperplastic and Colloidal Goitre in a Beetle Goat - Ravindran, R.; Bassessar, Varun; Syal, Priyanka; Punia, Sunil (International Journal of Bio-resource and Stress Management, 2024)
An investigation was conducted at the Veterinary Clinical Complex, College of Veterinary Science, COVS, GADVASU Rampura Phul, Punjab, India during May, 2023 to study the pathomorphological alterations of Hyperplastic and Colloidal Goiter in a beetal. Two new born kids were considered that included one dead and other with history of no suckling, lassitude, not able to rise its head and swelling in cranioventral neck region. Post mortem examination of dead kid showed markedly swollen thyroid gland and samples collected from them were subjected to routine H&E examination. Histopathological examination revealed extensive hyperplasia of the thyroid follicles along with follicles filled with varying amount of colloid suggesting hyperplastic and colloidal goitre. Areas of Hyperplastic follicles showed cuboidal to tall columnar follicular epithelial cells with highly vacoular cytoplasm whereas follicles with colloidal deposition showed flattened epithelium. Hemato-biochemical examination of samples collected from live kid showed moderate anaemia with decreased leucocyte count. There was macrocytic hypochromic anaemia. T4 was significantly lower and there was significant rise in TSH levels when compared to reference values. The kid born co-twin with the dead kid survived after treatment and showed significant improvement in clinical condition after 5 days of treatment. Based on the gross and histopathological examination the cause of death was confirmed to be congenital hyperplastic and colloid goitre which is usually a non-inflammatory and non-neoplastic enlargement of the thyroid caused due to iodine deficiency is most common in new-born animals in iodine-deficient areas.